Tailoring patients' enrollment in ALS clinical trials: the effect of disease duration and vital capacity cutoffs. Issue 1 (2nd January 2022) - Torrieri, Maria Claudia; Manera, Umberto; Mora, Gabriele; Canosa, Antonio; Vasta, Rosario; Fuda, Giuseppe; Salamone, Paolina; Grassano, Maurizio; Cugnasco, Paolo; Launaro, Nicola; De Marchi, Fabiola; Mattei, Alessio; et al.
Abstract: Objective: To evaluate how Amyotrophic Lateral Sclerosis (ALS) patients' mortality rates change, based on different levels of forced vital capacity (FVC) and disease duration, providing a scheme of mortality rates of a real population of ALS patients to improve the design of future RCTs. Methods : One random spirometry for each ALS patient was selected during four time intervals from disease onset: (1 ) ≤12 months; (2 ) ≤18 months; (3 ) ≤24 months; (4 ) ≤36 months. Date of spirometry corresponded to date of trial entry, while time interval onset-spirometry to disease duration at enrollment. Mortality rates from inclusion were computed at different time intervals. Based on progression rates, patients were stratified in slow, intermediate and fast progressors. Survival from recruitment was calculated depending on FVC, disease duration and progression rate. Results : We included 659 patients in group 1, 888 in group 2, 1019 in group 3 and 1102 in group 4. Mortality rates were higher in each group at reducing the FVC cutoff used for recruitment ( p < 0.001). Median survival decreased when lowering FVC and disease duration cutoffs ( p < 0.001); a higher median disease progression rate of included patients led to lower median survival from recruitment. The proportion of recruited fast progressors raised when shortening disease duration and lowering FVC cutoff. Conclusions : This is a simple model for setting eligibility criteria, based on mortality rates of patients depending on FVC and disease duration, to select the best population for RCTs, tailored to trials' primary endpoints and duration.